2008
DOI: 10.1021/ic800733x
|View full text |Cite
|
Sign up to set email alerts
|

Conformation Changes and Luminescent Properties of Au-Ln (Ln = Nd, Eu, Er, Yb) Arrays with 5-Ethynyl-2,2′-Bipyridine

Abstract: Reaction of polymeric gold(I) acetylide species (bpyC[triple bond]CAu)n (bpyC[triple bond]CH = 5-ethynyl-2,2'-bipyridine) with diphosphine ligands Ph2P(CH2)nPPh2 (n = 2-6) or 1,1'-bis(diphenylphosphino)-ferrocene (dppf) in dichloromethane induces isolation of binuclear gold(I) complexes (bpyC[triple bond]CAu)2{mu-Ph2P(CH2)nPPh2} or (bpyC[triple bond]CAu)2(mu-dppf). Complexation of Ln(hfac)3 (hfac = hexafluoroacetylacetonate, Ln = Nd, Eu, Er, Yb) subunits to the binuclear gold(I) complexes through 2,2'-bipyridy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 22 publications
2
71
0
Order By: Relevance
“…In fact, some research groups have recently described the synthesis of alkynyl gold(I) complexes with terminal 2,2′-bipyridine [41][42][43][44][45][46] or 2,2′:6′,2″-terpyridine units. 41,[47][48][49][50] Interestingly, however, in spite of the stability of these metallaligands, a limited number of reports on the supramolecular coordination chemistry of these species can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, some research groups have recently described the synthesis of alkynyl gold(I) complexes with terminal 2,2′-bipyridine [41][42][43][44][45][46] or 2,2′:6′,2″-terpyridine units. 41,[47][48][49][50] Interestingly, however, in spite of the stability of these metallaligands, a limited number of reports on the supramolecular coordination chemistry of these species can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Some years ago, Chen and co-workers described the isolation of tetrametallic Au 2 Ln 2 (Ln = lanthanide) arrays formed by the establishment of aurophilic interactions. 42 Very recently, Vicente and co-workers reported the obtention of appealing supramolecular architectures like triple-stranded helicates, 51,52 helical dimers, 53 rigid-rod complexes and coordination oligomers. 54 Noteworthily, all the reported alkynyl gold(I) compounds with pendant polypyridyl moieties mentioned above are supported by mono or diphosphanes as auxiliary ligands, and consequently are able to act as mono or ditopic metallaligands.…”
Section: Introductionmentioning
confidence: 99%
“…[3,[9][10][11] By combining phosphine and alkyne metal-binding domains at a gold(I) centre, one gains significant scope for the design of macromolecules: [12] rigid-rod P-Au-C≡C-domains and a wide range of readily accessible mono-, bi-and polydentate phosphine ligands containing sp 3 hybridized P atoms combine with a tendency for gold atoms to aggregate (so-called 'aurophilicity'). [13][14][15]16] Of the 215 compounds in the CSD (CSD v 5.3 with May 2009 updates, Conquest v. 1.11) [17] possessing R 3 PAuC≡C units, only 19 [9,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] exhibit intermolecular aurophilic interactions resulting in onedimensional Au...Au bonded polymers. Of particular relevance to our work is the trigold derivative ( n Bu 3 PAuC≡CCH 2 OCH 2 ) 3 CCH 2 Otpy (tpy = 2,2';6',2"-terpyridine) which forms one-dimensional chains with an oriented assembly in the solid state in which all the tpy units point in the same direction.…”
Section: Introductionmentioning
confidence: 99%
“…2018,24,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] www.chemeurj.org to six different metal centers, such as 57,t hrough severals uccessive metalloligand-to-metal coordination steps. [53] Alkynyl-gold metalloligands containing two bipyridyl units (58)w ere reported by the groups of Chen [54] andu s ( Figure 15). [48a, 55] Variation of the bridging ligand allows the easy modulation of the length and degree of flexibility of the metalloligand as wella st he synthesis of chiral metalloligands from chiral diphosphines.…”
Section: Metalloligands Containing Pyridine Binding Sitesmentioning
confidence: 97%
“…This was attributed to energy transfer from the excited Au-alkynyl luminophore to the [Ln(hfac) 3 (bpy)] unit. [54] We have reported that three metalloligands of the type 58 and two Fe 2 + ,C o 2 + ,o rZ n 2 + ions self-assemble to form triplestranded helicates 60 (Scheme 5). The X-ray structures of two of these M 2 Au 6 complexes showed that the helicate strands are folded, giving rise to at riple-looped structure, which is stabilized by Au···Au,C H···p,a nd p···p interactions (Scheme 5).…”
Section: Metalloligands Containing Pyridine Binding Sitesmentioning
confidence: 99%